Pre-conception and pre-natal diagnostic techniques (prohibition of sex selection) act, 1994 (57 of 1994) (New Delhi, 2012)
In the recent past Pre-natal Diagnostic Centres sprang up in the urban areas of the country using pre-natal diagnostic techniques for determination of sex of the foetus. Such centres became very popular and their growth was tremendous as the female child is not welcomed with open arms in most of the Indian families. The result was that such centres became centres of female foeticide. Such abuse of the technique is against the female sex and affects the dignity and status of women. Various Organisations working for the welfare and uplift of the women raised their heads against such an abuse. It was considered necessary to bring out a legislation to regulate the use of, and to provide deterrent punishment to stop the misuse of, such techniques. The matter was discussed in Parliament and the Pre-natal Diagnostic Techniques (Regulation and Prevention of Misuse) Bill, 1991 was introduced in the Lok Sabha. The Lok Sabha after discussions adopted a motion for reference of the said Bill to a Joint Committee of both the Houses of Parliament in September, 1991. The Joint Committee presented its report in December, 1992 and on the basis of the recommendations of the Committee, the Bill was reintroduced in the Parliament.
Keywords: Preconception and prenatal diagnostic techniques (prohib